Endoscopic Spring-Mediated Distraction for Unilambdoid Craniosynostosis. Issue 7 (October 2020) - Mittermiller, Paul A.; Rochlin, Danielle H.; Menard, Robert M.
Abstract : Background: Craniosynostosis treatment modalities have changed over time. These have included open calvarial remodeling, suturectomy with helmet molding, hand-powered distraction devices, and spring-mediated distraction. Implantable springs were first described for their use in treatment of craniosynostosis in 1998 (Lauritzen et al, Plast Reconstr Surg 121;2008:545-554). They have been used for the correction of craniosynostosis involving single and multiple sutures and have been placed through both endoscopic and open approaches. Their use for correction of lambdoid synostosis has been previously only described using an open approach (Arnaud et al, Child Nerv Syst 28;2012:1545-1549). The senior author has performed spring-mediated distraction for treating unilambdoid craniosynostosis using an endoscopic approach, which is described below and has not previously been reported by other authors. Methods: A retrospective analysis of our series of endoscopic unilambdoid synostosis repairs is included in this article. Patients were analyzed based on patient characteristics, operative details, and outcomes. The operation commences by approaching the lambdoid suture endoscopically through a 2- to 3-cm incision lateral to the lambdoid suture. Burr holes are placed on either side of the suture and a suturectomy is performed. Springs are bent preoperatively to a predetermined force. Two springs are placed across the suturectomy defect and the skin is closed. The patient is monitored for improvement in head shape and cranial X-rays are performed to measure the degree of distraction. Results: Seven patients underwent endoscopic spring-mediated distraction for unilambdoid craniosynostosis. The average age at the time of operation was 9.4 months. The median force of each spring placed was 7.0 N. The median length of hospital stay after spring placement was 2 days. Springs were removed at 5.6 months on average. Five patients had X-rays immediately after placement and prior to removal. Each spring expanded an average distance of 15.3 mm. There were no surgical complications. Three patients had both preoperative and postoperative computed tomography scans available. The angle of the cranial base, calculated by comparing foramen magnum to cribriform plate angles, improved 5.8° (12.3 preoperatively to 6.6 postoperatively). Conclusion: Endoscopic spring-mediated distraction is a safe and effective method of treatment for unilambdoid craniosynostosis. The series represents the largest experience with this technique. The approach can be considered in all patients with unilambdoid synostosis given the efficacious improvement in vault remodeling, low patient morbidity, short operating time, and minimal inpatient stay. Abstract : Supplemental Digital Content is available in the text